PENGARUH IKLIM ORGANISASI, KOMITMEN ORGANISASI DAN DUKUNGAN ORGANISASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA KARYAWAN LPD DI DESA ADAT PENARUNGAN - I Kadek Kicen Apriyana; Anak Agung Dwi Widyani; Ni Luh Gede Putu Purnawati (EMAS, 2021)
The attitude of employee behavior that is voluntary, sincere, happy without having to be ordered and controlled by the company in providing good service is known as the Organizational Citizenship Behavior (OCB). This study aims to determine the effect of organizational climate, organizational commitment, and organizational support on organizational citizenship behavior (OCB) among LPD employees in Penarungan Traditional Village by using a sample of 35 employees as research respondents. The sampling technique used in this study is the census method. Data collection was carried out through interviews and questionnaires. The data analysis technique used is multiple linear regression analysis processed using SPSS version 23 software. Based on the results of the analysis, this study shows that organizational climate, organizational commitment and organizational support have a positive and significant effect on organizational citizenship behavior (OCB) in LPD employees in the village. Traditional Penarungan. , , and